2019
DOI: 10.1038/s41396-019-0466-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ transformation of ethoxylate and glycol surfactants by shale-colonizing microorganisms during hydraulic fracturing

Abstract: In the last decade, extensive application of hydraulic fracturing technologies to unconventional low-permeability hydrocarbon-rich formations has significantly increased natural-gas production in the United States and abroad. The injection of surface-sourced fluids to generate fractures in the deep subsurface introduces microbial cells and substrates to low-permeability rock. A subset of injected organic additives has been investigated for their ability to support biological growth in shale microbial community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Multiple Halanaerobium species have been isolated from shale environments and exhibit thiosulfate-reducing capabilities (Ravot et al, 1997(Ravot et al, , 2005Fichter et al, 2012;Liang et al, 2014Liang et al, , 2016Booker et al, 2017). It appears more likely that thiosulfatereduction is the more prominent sulfidogenic pathway in fractured shale communities, as evidenced by the widespread presence of the thiosulfate-reducing bacterium Halanaerobium (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a;Strong et al, 2013;Cluff et al, 2014;Akob et al, 2015;Daly et al, 2016;Mouser et al, 2016;Vikram et al, 2016;Booker et al, 2017;Lipus et al, 2017;Borton et al, 2018;Evans et al, 2019).…”
Section: Persistent Sulfidogenic Taxamentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple Halanaerobium species have been isolated from shale environments and exhibit thiosulfate-reducing capabilities (Ravot et al, 1997(Ravot et al, , 2005Fichter et al, 2012;Liang et al, 2014Liang et al, , 2016Booker et al, 2017). It appears more likely that thiosulfatereduction is the more prominent sulfidogenic pathway in fractured shale communities, as evidenced by the widespread presence of the thiosulfate-reducing bacterium Halanaerobium (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a;Strong et al, 2013;Cluff et al, 2014;Akob et al, 2015;Daly et al, 2016;Mouser et al, 2016;Vikram et al, 2016;Booker et al, 2017;Lipus et al, 2017;Borton et al, 2018;Evans et al, 2019).…”
Section: Persistent Sulfidogenic Taxamentioning
confidence: 99%
“…Despite the addition of biocides and the extreme conditions encountered downhole including high salinity, pressure, reducing conditions, and moderately high temperatures (Fichter et al, 2012;Akob et al, 2015;Daly et al, 2016;Nixon et al, 2019) prior studies have identified microbial communities in produced waters from fractured shales in the Antrim, Barnett, Burkett, Utica, Bakken, and Marcellus formations in the United States (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a,b;Strong et al, 2013;Wuchter et al, 2013;Cluff et al, 2014;Akob et al, 2015;Daly et al, 2016;Liang et al, 2016;Lipus et al, 2017;Evans et al, 2018) as well as the Sichuan Basin in China (Zhang et al, 2017). A common finding in many of these studies, is a transition from high diversity microbial communities in injected fluids, resembling the freshwater environment the water was sourced from, to an enriched and lower diversity community of mostly halotolerant and halophilic facultative and strict anaerobes, such as Halanaerobium (Davis et al, 2012;Struchtemeyer and Elshahed, 2012;Murali Mohan et al, 2013a;Strong et al, 2013;Cluff et al, 2014;Akob et al, 2015;Daly et al, 2016;Mouser et al, 2016;Vikram et al, 2016;Booker et al, 2017;Lipus et al, 2017;Borton et al, 2018;Evans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on PEG and PPG degradation under aerobic conditions in sediment-groundwater microcosms amended with PW (Rogers et al, 2018), authors suggested that primary alcohol dehydrogenase (PA-DH) genes present in the dominant group Pseudomonas could explain the removal of PEG and PPG. Evans et al (2019) demonstrated that PPG, PEG and AEOs were likely to be degraded by pduCDE followed by pduP (aldehyde dehydrogenase gene) mapped to Halanaerobium in PW samples and in laboratory experiments with an isolate, Halanaerobium congolense WG10.…”
Section: Biocidesmentioning
confidence: 99%
“…These surfactants are generally present as a mixture of homologs and are identified by calculation of Kendrick mass defect from LC-MS data ( Thurman et al, 2014 ). A few recent studies have investigated biological attenuation of surfactants in the event of FPW spills ( Heyob et al, 2017 ; Rogers et al, 2018 ) or in natural-gas wells during production ( Evans et al, 2019 ) or during treatment for beneficial reuse ( Hanson et al, 2019 ). Heyob et al (2017) investigated removal of surfactants (Propylene glycol, PPG and commercial surfactants containing NPEOs, AEOs, and PPG-PEG co-block polymers) in soil-groundwater microcosms under anaerobic conditions.…”
Section: Compounds Of Concernmentioning
confidence: 99%